DINAMIKA PERUBAHAN TEMPERATUR DAN REDUKSI VOLUME LIMBAH DALAM PROSES PENGOMPOSAN (STUDI KASUS PENGOMPOSAN DI RPH CAKUNG – JAKARTA TIMUR) - Sri Wahyono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
The goal of this research is to study the dynamics changing of temperature, weight and volume of wastes during composting process in Cakung Slaughterhouse. The composting process was done using windrow system for 65 days. Windrow was turned mechanically using compost turning machine once a week. Composition of input wastes was calculated based on its volume and specific weight. Regularly, windrows were measured of their volume, weight and temperature. The composting shows that weight and volume reduction was exponentially done in the two of the first weeks. The temperature also exponentially increased in that time. Those indicated that the increasing of metabolisms and development of microbiology during composting process. Weight and volume reduction reached about 80 percent, and their temperature reached above 55oC during first weeks. The dynamics changing of the temperature and volume/weight reduction was the key parameter for evaluating composting process.